Biosourced Reduced Graphene Oxide and Its Application for Methylene Blue Adsorption - Rachmat, Addy; Ahadito, Bijak Riyandi; Suryani, Sri; Meiliza, Cici; Hidayati, Nurlisa; Julinar, Julinar; Said, Muhammad (Chemistry Department, The University of Brawijaya, 2025)
Graphene oxide and reduced graphene oxide have been widely studied as a biomass-sourced alternative to graphene for their various capabilities, e.g. as adsorbent. This publication reports the preparation of graphite (g), graphene oxide (GO), and reduced graphene oxide (rGO) from coconut shell (1) and sugarcane bagasse (2) using matoa leaves extract as reducing agent, characterized by XRD, FT-IR, and Raman spectroscopy. The X-ray diffractogram showed 2θ peaks between 22.8°–23.8° for g1, GO1, and rGO1, and between 23.6°–25.8° for g2, GO2, and rGO2. FT-IR spectra of both sets of GO and rGO showed common peaks of O–H ( 3400 cm–1), C–H ( 2900 cm–1), and C–OH ( 1600 cm–1), while also some noticeable differences between the sets. Raman spectra of both rGO showed D peak ( 1400 cm–1), G peak ( 1700 cm–1), and weak 2D peaks (2700–3300 cm–1) with ID/IG of 0.93 and 0.91 for rGO1 and rGO2, respectively. The obtained g, GO, and rGO were used as adsorbent for methylene blue dye. The adsorption study involved variation in dye concentration, contact time, and amount of adsorbent. It was found that rGO performs best as adsorbent compared to GO and g, with maximum adsorption capacity of 22.308 μg/mg (rGO1) and 47.533 μg/mg (rGO2). Adsorbents prepared from sugarcane bagasse were found to perform better due to its easiness of carbonization compared to coconut shell.